P19. Conformal segmented mono-isocentric radiotherapy vs. volumetric modulated arctherapy in senology. (December 2016) - Bodez, V.; Duqueyroix, F.; Fourvel, M.; Pradon, V.; Roux, V.; Mége, A.; Garcia, R.
Abstract : Introduction: Since 2005, the Conformal segmented mono-isocentric radiotherapy (3D-CRT) remains the standard treatment for all breast cancers in our center. However, volumetric modulated arctherapy (VMAT) may have an interest in irradiation of complex thoracic conformations. Material and methods: For pectus excavatum, 3D-CRT and VMAT treatment plans[1] were calculated on CT scanner managed with and without deep inspiration breath hold (DIBH). The prescribed dose to the breast volume was 50 Gy in 25 fractions. Plan normalization was such that 95% of the target volume received 95% of the prescribed dose. Eclipse™ treatment planning system (Varian Medical Systems) and Anisotropic Analytical Algorithm (AAA) were used in this study. The field arrangement was based on two segmented opposed tangential fields in 3D-CRT, 3 arcs in VMAT and 5 arcs in DIBH VMAT. The mono-isocentric technique required direct optimization by a "Field in Field" method useful to replace the enhanced dynamic wedge unusable in quarter beams. Unlike the 3D-CRT technique, where the outer opening of the tangential fields takes into account the respiratory movements and anatomical changes (edema), the body contour on CT scanner used for inverse VMAT planning had to be artificially expanded. The optimized plan was then pasted on the initial CT and calculated keeping the monitor units obtained on the extended scanner calculation[2] . Results: The main organs at risk (OAR) for this pathology were both healthy lungs (Healthy L), the healthy ipsilateral lung (healthy ILL), the heart and the contralateral breast (CL breast). For this OAR, the characteristic parameters such as the volume receiving 20 Gy (V20 Gy) or 30 Gy (V30 Gy), the mean dose (Dmean ), or the dose at 2% of the volume (D2%), were recorded. They were analyzed according to the criteria noted in the table below. VMAT planning meets all the dosimetric validation criteria and allows better lung sparing. In contrary, even if the criteria are acceptable, the heart is less protected by this technique. The major benefit provided by the VMAT technique remains the contralateral breast protection. Conclusion: This dosimetric comparison shows that the volumetric modulated arctherapy is benefic for treating specific conformations like funnel chest, with a better OAR sparing. This comparison should be made for the treatment of left side breast with lymph node, and for thin and concave thoracic walls.